1986
DOI: 10.1159/000234163
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Murine IgE Responses with Amino Acid Polymer/Allergen Conjugates

Abstract: Conjugates of poly-N-methylglycine (polysarcosine) and grass pollen extracts, previously found to be capable of suppressing immature IgE antibody responses in mice, were shown to be highly effective at inhibiting the capacity of immune splenocytes to produce a secondary response in sub-lethally irradiated recipient animals. Anamnestic IgE responses in mice primed without adjuvant were also suppressed, but the effects were modest and of short duration. The predictive value of murine models for selecting clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Intravenous treatment of mice with conjugates of polysarcosine-allergen have previously been shown to suppress the induction of an IgE response and to impair a secondary response in sub-lethally irradiated recipients [11,19]. Activity was demonstrated to be specific and was maintained in the absence of further challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous treatment of mice with conjugates of polysarcosine-allergen have previously been shown to suppress the induction of an IgE response and to impair a secondary response in sub-lethally irradiated recipients [11,19]. Activity was demonstrated to be specific and was maintained in the absence of further challenge.…”
Section: Discussionmentioning
confidence: 99%
“…We have described previously the suppressive ef fects of conjugates of poly-N-methyl glycine (polysarcosine)-grass pollen extracts on the induction and maintenance of IgE responses in mice [11,19,20]. The present report is concerned with the effects of these conjugates on lymphocyte activity in culture, and possible mechanisms of action are discussed.…”
Section: Introductionmentioning
confidence: 91%
“…The suppression is allergen-specific and requires covalent linking of the polysarcosine to the allergen. [92] The reduced IgE response was transient [93] and was attributed partly to a short-lived antigen-specific T cell suppression. [94] It was further demonstrated that intranasal application of the conjugate can reduce the serum IgE antibody response that was brought about through exposure to the grass pollen extract, [95] providing a method to treat allergy.…”
Section: Immunogenicitymentioning
confidence: 99%
“…Such conjugates have been shown to have the capacity to sup press IgE antibody responses in mice [13,19].…”
Section: Conjugate Of Polysarcosine and Mixed Grass Pollen Extractmentioning
confidence: 99%
“…In addition, we have shown that tolerogenic forms of pollen allergen, conjugates of grass pollen extracts and polysarcosine, poly-(N-methylglycine), given parenterally to mice, were capable of suppressing spe cific IgE antibody production [13,19,20], These find ings indicated that continuous therapy with such tolerogens during the period of environmental exposure to allergen could prevent the seasonal boost of IgE antibody production and concomitant heightened sensitivity in susceptible individuals. The problems associated with systemic therapy may be avoided by use of the intranasal route and, therefore, we have ex plored the possibility of suppressing IgE responses in mice by intranasal administration of these tolerogenic preparations.…”
Section: Introductionmentioning
confidence: 99%